2019
DOI: 10.1027/1864-1105/a000246
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Consumption and Sexual Satisfaction in a Korean Sample

Abstract: Abstract. This research report assessed pornography consumption and sexual satisfaction in a heterosexual sample of Korean adults. Consistent with prior studies, the linear association between pornography consumption and satisfaction was negative and significant. However, the addition of a quadratic term to the equation increased model fit. Interaction effect analyses revealed an inverted U relationship for both men and women, such that occasional pornography consumption was associated with higher satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Several elements of the present study point to directions for subsequent research. First, although comparisons of dichotomous and interval pornography consumption measures suggest that both yield theoretically anticipated results (Wright, 2022; Wright et al, 2017; Wright, Tokunaga, Herbenick, et al, 2022b), dichotomous measures may attenuate effect sizes (Bland & Altman, 2011; Bogaert et al, 1999) and also preclude assessments of possible curvilinear relationships between pornography use and sociosexual outcomes (Willoughby et al, 2021; Wright, Bridges, et al, 2018; Wright, Miezan, et al, 2019; Wright, Steffen, et al, 2019). Subsequent replicative studies should include interval indices of pornography consumption (e.g., Peter & Valkenburg, 2008, 2009, 2010) to see if larger effect sizes ensue and to probe for nonlinear interactions between pornography consumption and political ideology on sexually permissive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Several elements of the present study point to directions for subsequent research. First, although comparisons of dichotomous and interval pornography consumption measures suggest that both yield theoretically anticipated results (Wright, 2022; Wright et al, 2017; Wright, Tokunaga, Herbenick, et al, 2022b), dichotomous measures may attenuate effect sizes (Bland & Altman, 2011; Bogaert et al, 1999) and also preclude assessments of possible curvilinear relationships between pornography use and sociosexual outcomes (Willoughby et al, 2021; Wright, Bridges, et al, 2018; Wright, Miezan, et al, 2019; Wright, Steffen, et al, 2019). Subsequent replicative studies should include interval indices of pornography consumption (e.g., Peter & Valkenburg, 2008, 2009, 2010) to see if larger effect sizes ensue and to probe for nonlinear interactions between pornography consumption and political ideology on sexually permissive attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that watching pornography, both those pornographic materials described as "problem atic" and "nonproblematic", does not have negative correlations with one's own satisfaction with life, but nevertheless has a negative impact on the satisfaction with close romantic relations [9]. However, what is in teresting, it is indicated that occasional pornography use improves sexual satisfaction, while more frequent pornography use worsens it [10]. A hypothesis that can explain the described phenomenon is viewing such pornographic materials, the implementation of which is not possible in reality, and which becomes the point of reference of the target sexual contact for a given person.…”
Section: Wprowadzeniementioning
confidence: 99%
“…Wskazuje się, że oglądanie pornografii, zarówno określane jako "problematyczne", jak i "nieproblematycz ne", nie wiąże się negatywnie z własną satysfakcją z życia, niemniej wpływa negatywnie na satysfakcję z bliskich związków romantycznych [9]. Co jednak interesujące, wskazuje się, że sporadyczne użytkowanie pornogra fii poprawia satysfakcję z życia seksualnego, natomiast częstsze użytkowanie -pogarsza ją [10]. Hipotezą mo gącą tłumaczyć opisane zjawisko jest oglądanie takich materiałów pornograficznych, których realizacja nie jest możliwa w rzeczywistości, a staje się ona punktem odnie sienia docelowego kontaktu seksualnego dla danej osoby.…”
Section: Wprowadzenieunclassified
“…Although these studies yield important findings, they do not explore other relevant elements, such as the type of pornography used or the associated discomfort. First, viewing erotic material has been associated with sexual well-being and sexual satisfaction between heterosexual couples (Maas et al, 2018), especially when it is occasional (Wright et al, 2019). Such viewing can be used to learn about sexual matters (Ševčíková & Daneback, 2014), provide greater sexual openness and better sexual experiences (Rissel et al, 2017), and serve as ways to discover preferences and develop intimacy (Attwood et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, a higher and more regular consumption of pornography has also been associated with sexual dissatisfaction (Blais-Lecours et al, 2016;Wright et al, 2019). In particular, some authors have related the viewing of pornography with greater discussions (Carroll et al, 2017) and worse sexual quality within a couple (Poulsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%